SnO2 nanoparticle synthesized by ultrasonic-assisted process - Noonuruk, Russameeruk; Mekprasart, Wanichaya; Wongpisutpaisan, Narongdet; Vittayakorn, Naratip; Pecharapa, Wisanu (My University, 2013)
SnO2 nanoparticles were synthesized by ultrasonic-assisted precipitation process using stannic chloride pentahydrate (SnCl4·5H2O) as a precursor. The stannic chloride aqueous solution was precipitated by ammonia under sonication. The as-synthesized precipitates were dried at 80 °C and then calcined at 400 °C for 2 h. The physical properties of nanoparticles with/without sonication were characterized by thermogravimetic and differential thermal analysis, X-ray diffraction, and transmission electron microscope. The results reveal that ultrasonic radiation has significant influence on phase transformation mechanism from Sn(OH)4 to SnO2, grain size and uniformity of SnO2 nanoparticles. © (2013) Trans Tech Publications, Switzerland.
Keywords: Precipitation; SnO2 nanoparticles; Ultrasonic-assisted